Socio-Cultural Dynamics of Coastal Communities of North West Java in The Midst of Modernization: A Case Study the Nadran Tradition in Coastal Communities of Cirebon - Kheysa Dwinanda Agustina; Mulyanie, Erni; Muhammad Asyroful Mujib; Iya’ Setyasih (Universitas Negeri Surabaya, 2025)
The Nadran tradition in the coastal community of Cirebon, West Java, is a form of local wisdom that has existed for a long time and is an integral part of their social and cultural life. This study discusses the socio-cultural dynamics of the coastal community of North West Java amidst modernization, with a focus on the Nadran tradition in the coastal community of Cirebon. This study uses a literature study method with a qualitative approach to explore how the Nadran tradition is maintained, changed, and integrated into the increasingly modern life of society. The findings of this study indicate that the Nadran tradition not only functions as a ritual of gratitude for fishermen for marine products, but also as a means of strengthening social ties and cultural identity amidst rapid social change. On the other hand, modernization brings challenges and opportunities for the sustainability of this tradition. The results of this study are expected to provide insight into efforts to preserve local culture in the context of sustainable modernization.